Political Correctness and the Obfuscation of Politics - Ohmann, Richard (Radical Teacher, 2022)
During the PC spasm last year I was talking regularly with friends on the board of this magazine, with colleagues at Wesleyan planning for cultural studies there, and with a group of left academics from colleges and universities in southern New England. We spent a good deal of time grousing about the assault on "political correctness" and multiculturalism, and trying to understand the phenomenon. What follows is an attempt to voice some of the exasperation we felt and sketch a "position" that was nowhere heard in the mainstream media. It came directly out of talks with my political friends, though of course I don’t claim to speak for them. We lefties are not that keen for what often presents itself as multiculturalism. There is a version of it that takes the people of the world to be parceled out into cultures and subcultures, each self-contained and uniform, and each accessible only to its members–so that, for instance, only a Chicana would have the authority to teach about Chicana poetry. On the contrary, we think that all cultures are in continuous exchange with others, and that even the smallest societies are not homogeneous, but embrace their own hierarchies and conflicts. The search for purity is futile. Worse, it precludes learning about cultures from outside and certifies only the "other" as a source of knowledge about other cultures. It also tends to valorize raw experience as the only foundation of knowledge, and to forbid critique of cultures except from within. This sort of multiculturalism sees people as just intrinsically what they are–black lesbians, white male heterosexuals, and so on. Its essentialism is almost as disturbing to us as is the fatuous universalism of the right. On top of that, it leads to a politics of identity that makes any sort of embracing social movement against capitalist patriarchy hard indeed to imagine. The fact that multiculturalism has become a slogan of many college administrations and funding sources suggests how unthreatening it is to the holders of power, and how easy to contain and control in the guise of "diversity," not to mention its usefulness in training global corporate managers. Much about the PC phenomenon drives us up the ivied walls. Censorship, of course: we’ll all take a loyalty oath to free speech. I pay dues to the American Civil Liberties Union and endorse most of its positions. And if it’s OK for the Klan to speak on campus, it’s surely OK for our National Association of Scholars colleagues to teach their classes (with unaccustomed responsibility for their ideas, of course). The few incidents of actual censorship, however, incidents recycled endlessly through the media, and those of egregious bad manners (with no censorship involved) that draw headlines like "Return of the Storm Troopers" (Wall Street Journal, April 10, 1991), are not what we mainly hold against PC, much as we deplore them. We object to PC because it is often a self-indulgent substitute for politics, a holier-than-thou moralism of the converted. PC is attitude politics, a politics of feeling good, a politics of surfaces and gestures that in its extreme form amounts to a conviction that the ills of the social order will be cured when executives no longer call their secretaries "girls" and thin people stop using the word "fat." As the right correctly (!) perceives, this is also a politics of separate issues, a catechism that can be memorized by sophomore year, a "cluster of opinions about race, ecology, feminism, culture, and foreign policy" (Richard Bernstein, New York Times, October 28, 1990).